2017
DOI: 10.1016/j.tox.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure-skin permeability relationships

Abstract: Quantitative Structure -Skin permeability Relationships http://researchonline.ljmu.ac.uk/6719/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitate their private study or for non-commercial research. You may not engage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 107 publications
(13 reference statements)
0
52
0
Order By: Relevance
“…A compound can permeate the stratum corneum by the intercellular, transcellular or appendageal routes, according to its size and its chemico-physical properties 5,6 . Skin permeability is widely recognized as an essential parameter to be considered for the delivery of active substances 1 , but it is also considered important for risk assessment purposes 7 . Guidelines for in vitro and in vivo skin permeation tests have been drafted by the OECD 8,9 , but no universal protocol has been developed.…”
Section: Skin Permeationmentioning
confidence: 99%
See 2 more Smart Citations
“…A compound can permeate the stratum corneum by the intercellular, transcellular or appendageal routes, according to its size and its chemico-physical properties 5,6 . Skin permeability is widely recognized as an essential parameter to be considered for the delivery of active substances 1 , but it is also considered important for risk assessment purposes 7 . Guidelines for in vitro and in vivo skin permeation tests have been drafted by the OECD 8,9 , but no universal protocol has been developed.…”
Section: Skin Permeationmentioning
confidence: 99%
“…Moreover, it is impossible to evaluate compounds not yet synthetized. Hence, it is crucial to use an efficient and accurate in silico model of human skin permeability in order to reduce product development costs in early stage screening 10 , resolve ethical issues, understand the 2 mechanisms of absorption 1 , and reduce measurements variability. In fact, it has been shown that the skin permeability can variate inter-and intra-subject 11 .…”
Section: Skin Permeationmentioning
confidence: 99%
See 1 more Smart Citation
“…through extraction or fluidization of the lipid bilayer) or could cause irritation and/or corrosion. A step forward in that direction could be the examination of models developed specifically for transdermal enhancers, as discussed in Tsakovska [53]. Unfortunately, these latter approaches could not be examined against our dataset due to a lack of detailed information on formulation composition, which is usually treated as confidential business information in the case of plant protection products.…”
Section: Occlusion After Applicationmentioning
confidence: 99%
“…Physicochemical properties such as the molecular weight and partition coefficients (log P) may inform possible penetration through skin and other tissues. Several QSPRs (Quantitative Structure-Property-Relationships) for skin penetration have been developed on this basis (Dumont et al [16] , recent review of computational skin permeability models: Tsakovska et al [90] ). Volatility must be considered in the exposure scenario and determination made of whether it is possible to exclude intake through inhalation.…”
Section: A Workflow For Chemical Safety Assessment With Non-animal Mementioning
confidence: 99%